Ћамил-паша у Босни и Херцеговини у 1853. години - Šljivo, Galib (Balcanica - Annual of the Institute for Balkan Studies, 1979)
Ćamil Pasha's 1853 Mission to Bosnia and Herzegovina The two-year administration by Omer pasha in Bosnia and Herzegovina influenced only partially the appeasement of situation. After his retreat from Bosnia, the Austrian consul general describes again in his reports many irregularities and misuses done by the representatives of sultan's administration in Bosnia.